Respostas

A melhor resposta!
  • Usuário do Brainly
2014-04-11T17:53:27-03:00
Temos então:

a.
A(1,2)
B(2,4)

Xm=x1+x2÷2
Xm=1+2÷2
Xm=3/2

Ym=y1+y2÷2
Ym=2+4÷2
Ym=6÷2
Ym=3

M(3/2,3)

b.
C(3,5)
D(2,-3)

Xm=x1+x2÷2
Xm=3+2÷2
Xm=5/2

Ym=y1+y2÷2
Ym=5+(-3)÷2
Ym=5-3÷2
Ym=2÷2
Ym=1

M(5/2,1)

c.
E(-1,-1/2)
F(-3,3/2)

Xm=x1+x2÷2
Xm=-1+(-3)÷2
Xm=-1-3÷2
Xm=-4÷2
Xm=-2

Ym=y1+y2÷2
Ym=-1/2+3/2÷2
Ym=2/2÷2
Ym=2/4

M(-2,2/4)

d.
G(-3,5)
H(3,-5)

Xm=x1+x2÷2
Xm=-3+3÷2
Xm=0

Ym=y1+y2÷2
Ym=5+(-5)÷2
Ym=5-5÷2
Ym=0

M(0,0)

1 5 1